Diverse expression pattern of wheat transcription factors against abiotic stresses in wheat species - Baloglu, Mehmet Cengiz; Inal, Behcet; Kavas, Musa; Unver, Turgay (Elsevier BV, 2014)
Abiotic stress including drought and salinity affects quality and yield of wheat varieties used for the production of both bread and pasta flour. bZIP, MBF1, WRKY, MYB and NAC transcription factor (TF) genes are the largest transcriptional regulators which are involved in growth, development, physiological processes, and biotic/abiotic stress responses in plants. Identification of expression profiling of these TFs plays a crucial role to understand the response of different wheat species against severe environmental changes. In the current study, expression analysis of TaWLIP19 (wheat version of bZIP), TaMBF1, TaWRKY10, TaMYB33 and TaNAC69 genes was examined under drought and salinity stress conditions in Triticum aestivum cv. (Yuregir-89), Triticum turgidum cv. (Kiziltan-91), and Triticum monococcum (Siyez). After drought stress application, all five selected genes in Kiziltan-91 were induced. However, TaMBF1 and TaWLIP19 were the only downregulated genes in Yuregir-89 and Siyez, respectively. Except TaMYB33 in Siyez, expression level of the remaining genes increased under salt stress condition in all Triticum species. For determination of drought response to selected TF members, publicly available RNA-seq data were also analyzed in this study. TaMBF1, TaWLIP19 and TaNAC69 transcripts were detected through in silico analysis. This comprehensive gene expression analysis provides valuable information for understanding the roles of these TFs under abiotic stresses in modern wheat cultivars and ancient einkorn wheat. In addition, selected TFs might be used for determination of drought or salinity-tolerant and susceptible cultivars for molecular breeding studies.
Keywords: Salinity; Time Factors; Drought; Reverse Transcriptase Polymerase Chain Reaction; Sodium Chloride; Droughts; Gene expression analysis; Species Specificity; Transcription factor genes; Gene Expression Regulation, Plant; Wheat; Computer Simulation; Transcriptome; Triticum; Plant Proteins; Transcription Factors; 2. Zero hunger; 15. Life on land; 6. Clean water; 13. Climate action